Silicone Turbidity Monitoring System Using IoT for Extruder Machine: Sistem Pemantauan Kekeruhan Berbasis Silikon yang Menggunakan IoT untuk Mesin Ekstruder - Andra Erlangga; Arief Wicaksono (Universitas Muhammadiyah Sidoarjo, 2026)
This study presents a real-time monitoring system for silicone turbidity in an industrial extruder process. General Background: Quality control in manufacturing processes requires accurate monitoring systems to prevent product defects caused by inconsistent material composition. Specific Background: In silicone coating processes, improper silicone-to-water ratios can result in sticky or overly slippery film surfaces. Knowledge Gap: Conventional monitoring methods rely on manual observation, which is inefficient and prone to human error. Aims: This research aims to design and implement an IoT-based turbidity monitoring system to ensure optimal silicone mixture conditions. Results: The system utilizes a turbidity sensor SEN0189 integrated with NodeMCU ESP8266, displaying data via LCD and ThingSpeak platform, successfully identifying optimal ratios between 1:20 and 1:25 and triggering alarms for abnormal conditions. Novelty: The integration of real-time turbidity sensing with IoT-based remote monitoring and automated alert system provides a digital solution for industrial quality control. Implications: This system supports efficient monitoring, reduces manual inspection, and contributes to digital transformation in manufacturing aligned with Industry 4.0 principles. Keywords: Silicone Turbidity, IoT Monitoring, NodeMCU ESP8266, Industrial Quality Control, Turbidity Sensor Key Findings Highlights Real-time detection distinguishes optimal and defective mixture conditions Remote visualization enables continuous supervision without physical presence Automated alert system signals deviations from predefined standards